Total glossectomy in multimodal treatment of oropharyngeal cancer: immediate results - D. V. Sikorsky; S. O. Podvyaznikov; N. V. Kanishcheva; M. V. Kuligin; D. V. Skamnitsky (Опухоли головы и шеи)
The study objective is to analyze the results of combined antitumor therapy, which included glossectomy, to treat locally advanced and recurrent oropharyngeal squamous cell cancer.Materials and methods. We performed a retrospective analysis of multimodal antitumor therapy of 19 patients, who were treated in the Nizhny Novgorod Regional Clinical Oncologic Dispensary within 2009–2019. All patients underwent segmental resection of the mandible due to massive tumor invasion into the periosteum. After total glossectomy the defect was filled using pectoralis musculocutaneous flap. Due to the wide local tumor spread, a neck dissection (n = 7) or radical cervical lymphadenectomy (n = 12) were performed. During preventive surgery, metastases that were not detected before surgery were revealed in 2 patients in 1 neck lymph node. Results. Eleven patients had local purulent-necrotic postoperative complications. It was noted that after surgery but without radiation therapy complications developed in fewer patients (n = 4) and were less severe: of I degree – in 3 patients, of III degree – in 1 patient. Radiation therapy before surgery resulted in more severe purulent-necrotic complications in 7 patients: of I degree – in 2 patients, of II degree – in 1, of III degree – in 4. Mortality rates: 30-day, 60-day and 90-day – 10.5 %, 21 % and 37 %, respectively. The causes of death were complications of gastrostomy: profuse bleeding from the stomach wall (n = 1), acute psychosis complicated by cerebral edema (n = 1), increased heart failure (n = 1), necrosis of the anterior abdominal wall and cachexia, developed after gastrostomy (n = 1), continued tumor growth between chemotherapy courses (n = 3). Twelve patients survived more than 90 days after surgery, 3 patients – more than 2 years. As most of the patients could not swallow, they were administered a nasogastric tube, since a simultaneous gastrostomy increases the duration of a traumatic operation and aggravates the postoperative period.Conclusion. Multicomponent surgery after radiation therapy results in more often local purulent-necrotic postoperative complications than if the surgery is performed before radiation therapy. High mortality in the first 90 days after surgery (n = 7) due to local cancer spread is generally determined by the severe condition of patients with advanced cancer and the concomitant diseases. However, rejection of gastrostomy in favor of nasogastric tube seems reasonable, since several deaths in the early postoperative period may be occurred due to complications associated with gastrostomy.